Autopsy findings in sudden death in adults: a study of 150 cases - Modi, Rahul A.; Patel, Mubin I.; Patel, Mandakini M.; Padsala, Suresh; Chaudhary, Jainisha (International Journal of Research in Medical Sciences, 2020)
Background: World Health Organization (WHO) deﬁnes sudden death as “deaths within 24 hours from the onset of the symptoms”. It is also deﬁned as death, which is sudden, unexpected, clinically unexplained. Aims of the study was to classify underlying causes of sudden death, to find out risk factors, associated diseases and triggers of sudden deaths in the autopsy specimens received in the Department of Pathology, Government Medical College, South Gujarat. Methods: A review of autopsies of sudden deaths performed between January 2018 to August 2018 in age group 15-45 years at Department of Pathology, Government Medical College, South Gujarat were done. Results: A total of 150 cases were studied for sudden deaths during the study. The age ranged from 15 to 45 years. Maximum deaths occurred in the age group between 35-45 years. Males (n=120) were affected more than females (n=30). The cause of deaths in 84 cases (56%) were attributed to cardiac causes and the remaining cases (44%) were due to noncardiac causes like pulmonary diseases (17.3%) followed by hepatobiliary diseases (5.4%), cerebrovascular (2%) and others like suicide by ingestion of poisoning, hanging and asphyxia (9.3%). Major cardiac cause for sudden deaths was Coronary Artery Disease (CAD) (95.2%). Conclusions: Sudden deaths were common in young adults and most are attributed to a cardiac cause. This study highlights the serious health concern in our society and a necessity to create awareness among the population at risk so that sudden deaths can be averted and life expectancy can be improved.